YIELD PERFORMANCE OF MUSK MELON (CUCUMIS MELO L.) AS INFLUENCED BY INTRA-ROW SPACING AND POULTRY MANURE RATE IN SAVANNA ZONE OF NIGERIA - Abubakar Ladan, Ibrahim; Adesoji, Aderemi G.; Jari, Sanusi (FUDMA Journal of Sciences, 2026)
Bilocation trials were conducted during the 2023 rainy season in Dutsin-Ma, Sudan Savanna ecological zone and Malumfashi, Northern Guinea Savanna ecological zone, Nigeria, to determine the yield response of Musk melon (Cucumis melo L.) varieties to intra-row spacing and poultry manure. The treatments comprised 2x3x4 factorial combinations of two musk melon varieties (NEPTUNE F1 and URANUS F1), three intra-row spacing treatments (25cm, 50cm, and 75cm), and four poultry manure rates (0, 5, 10, and 15 tons/ha). A Randomized Complete Block Design (RCBD) with three replications was used. URANUS F1 significantly (P<0.05) hastened flowering compared with NEPTUNE F1. URANUS F1 produced significantly (P<0.05) higher fruit weight/plant and fruit yield/plant than NEPTUNE F1 in Malumfashi. 75cm intra-row spacing produced significantly (P<0.05) higher fruit diameter and fruit weight/plant than other intra-row spacings. 75cm intra-row spacing produced significantly (P<0.05) higher fresh fruit yield/hectare than other intra-row spacings in Dutsin-Ma, but 50cm intra-row spacing produced significantly (P<0.05) higher fresh fruit yield/hectare than other intra-row spacings in Malumfashi. Applying 15 t poultry manure ha-1 produced significantly (P<0.05) higher fruit diameter, fruit weight/plant and fresh fruit yield/hectare than other rates. Interaction between intra-row spacing and poultry manure was significant on fresh fruit yield/hectare, where 50cm intra-row and 15 t poultry manure ha-1 produced significantly higher fruit yield/hectare than other combinations. In conclusion, sowing NEPTUNE F1 in Dutsin-Ma and URANUS F1 at Malumfashi at 50cm intra-row spacing and 15 t poultry manure ha-1 is the most suitable for musk melon yield in the study area.